A Controlled Evaluation of a Sport-Specific Performance Optimization Program in an Athlete Diagnosed With Attention Deficit Hyperactivity Disorder and Oppositional Defiant Disorder Within the Context of COVID-19. (June 2022) - Phrathep, Davy; Donohue, Brad; Kraus, Shane; Paul, Michelle; Mercer, John
Adolescent athletes with attention deficit hyperactivity disorder (ADHD) and oppositional defiant disorder (ODD) experience unique challenges that impact their sport performance, such as making errors due to poor concentration. The current multiple-baseline across behaviors case trial (i.e., positive assertion and negative assertion) is an evaluation of The Optimum Performance Program in Sports in an adolescent athlete diagnosed with ADHD and ODD. Intervention skill sets were targeted sequentially in a virtual format to safeguard against COVID-19 contraction. A battery of psychological measures was administered at baseline, post-intervention, and 1-month follow-up. Results indicated negative and positive assertion skills improved, but only when targeted, and severity of ADHD and ODD symptom severity, general mental health symptoms, and factors interfering with sport performance decreased from pre- to post-intervention and these improvements were maintained at 1-month follow-up. Similar improvements occurred in relationships with coaches, teammates, and family. Treatment integrity and consumer satisfaction were high.